PENGARUH PROPORSI MARGARIN DAN PUREE PISANG AMBON SEBAGAI FAT MIMETIC TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK REDUCED FAT STEAMED BROWNIES - Ong, Florence; Widjajaseputra, Anna Ingani; Trisnawati, Chatarina Yayuk (Jurnal Teknologi Pangan dan Gizi, 2015)
Fat reduction on brownies can alter sensory properties of the product, so a fat mimetic like green banana puree was needed to replace some fat. This research aims to determine the effect of the proportion of margarine which is replaced with green banana puree on physicochemical and sensory quality of steamed brownies. Randomized Block Design with one factor (margarine:banana puree) was used in this research which consist of six level (margarine:banana puree = 100:0, 60:40, 55:45, 50:50, 55:45 and 40:60) with four replications. The product was evaluated for water content, reducing sugar content, fat content, specific volume, cohesiveness, and sensory properties. All of the data were analyzed by Analysis of Variance (Î± 5%). Duncan Multiple Range Test (Î± = 5%) was used to determine the significant difference among the treatments. The proportion of margarine and green banana puree treatment gives a significant difference (Î± = 5%) on water content, reducing sugar content, fat content, specific volume and organoleptic properties of steamed brownies: but no real influence on cohesiveness steamed brownies. The most preferred steamed brownies with proportion of margarine: banana puree 45:55 which has 33.51% moisture content; 4.69% reducing sugar content; 12.31% fat content; specific volume 2.3401 cm3/g, cohesiveness 0.7173 cm/g/s, softness preference 5.38 (somewhat liked ïƒ¨ liked), 5.41 flavor preference (somewhat liked ïƒ¨ liked), 5.30 tenderness preference (somewhat liked ïƒ¨ liked) and moistness preference 5.01 (somewhat liked).